Agronomy Ontology (AgrO) - CGIAR Platform for Big Data in Agriculture (2019)
The Agronomy Ontology (AgrO) has been created, is interoperable with existing ontologies and is openly available online. It is now in an improvement phase where we already started the integration of users' feedback. Partners have also already started to use the ontology.